Cycle Link : procurement in Europe - Yue, Tao, active 2012; Yang, Shengyun, active 2012 (London : Rotterdam School of Management, Erasmus University, 2012)
Cycle Link Europe moved its European headquarters to Rotterdam, the Netherlands, in 2011 after experiencing difficulties in Germany. The company purchased and exported recovered paper from Europe to China for its own production needs. Its strategy in Europe was to outperform competitors in service areas by implementing timely pickup of goods, continual purchase, and in-time payment tactics. Since superior service was a competitive advantage, Cycle Link Europe needed good people and reliable suppliers. However, working with Western employees and suppliers did not always run smoothly - communication sometimes experienced glitches.
Originally Published In : Yue, T., & Yang, S. (2012). Internationalization Strategy of Chinese Private Enterprises in Europe-Case Series: Cycle Link: Procurement In Europe. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Industrial procurement -- Europe -- Case studies